ANALISIS PENDAPATAN DAN STRATEGI PENGEMBANGAN USAHA BUDIDAYA IKAN NILA DI KECAMATAN AMPANA KOTA KABUPATEN TOJO UNA-UNA - Siti Hadijah; Muhammad Basir-cyio; Lien Damayanti (Universitas Tadulako, 2015)
This research aimed to determine the income of farmers and to determine the strategy for developing Tilapia fish culture business inAmpana Kota sub districtof TojoUna-Una Regency. The research location was purposively selected as Ampana Kota sub district has a fairly extensive area of Tilapia fish culture compared to the other sub districts in TojoUna-Una regency.Respondents of 63 people were selected using a census method.Data collected was analyzed using income, SWOT and QSPM analysis. The results showed that the average of income is IDR 11,667,608/ha/harvest season. The aquaculturebusiness development strategy that can be implemented is SO strategybased on the SWOT matrix with a score of 3.255. This strategy utilizesgovernment assistance in order to optimize the performance of aquaculture farmer groups. Various programs that can be applied including training for optimizing and increasing production, developing distribution channels and expandingmarketing channels, and increasing land potency for expanding the aquaculture to meet increasing demand of Tilapia consumption. The QSPM analysis suggested that the best program for the development of the Tilapia culture inAmpana Kota sub district is the second program “the development of distribution channels and expand marketing channels” with a total value of attractiveness (TAS) of 5,216.Keyword : Income, QSPM, SWOT, Tilapia Fish.